Analyses of the Applicability of International Arbitration in Investor-State Dispute Settlement in East Africa - Antai, Godswill Owoche; Obisesan, Olawunmi Opeyemi; Umo, Maria Edet; Okonji, Charles Ifeasinachi; Okpong, Dennis Edet (NIU Journal of Humanities, 2025)
This study delves into the practical implementation of international arbitration within the Investor-State Dispute Settlement (ISDS) framework across East African countries. It examines the complex interplay between regional legal structures and international arbitral norms, scrutinizing the extent to which existing treaties and domestic legislation facilitate or hinder effective dispute resolution. Focusing on recent ISDS cases, the research analyses the procedural and substantive challenges faced by both investors and states, particularly concerning transparency, enforcement of awards, and the influence of regional economic communities. The analysis further evaluates the impact of varying levels of institutional capacity and legal harmonization on the predictability and fairness of arbitral outcomes. The article also further identifies best practices and potential reforms aimed at enhancing the efficacy and legitimacy of international arbitration as a tool for resolving investment disputes in the region. It underscores the critical need for context-specific adaptations of international arbitration to reflect the unique legal and economic realities of East Africa. Keywords:  Arbitration, Investor-State Dispute Settlement (ISDS), Investment Disputes